Studies on the preparation of lead(II) chloride from galvanizing plant wastes (Bangladesh Journal of Scientific and Industrial Research, 2013)
Galvanizing plant wastes containing 71.82% lead was leached in hydrochloric acid. Lead was precipitated from the leach liquor as lead chloride and purified by recrystallisation. The process parameters like concentration of hydrochloric acid, time of leaching, mode of reaction, number of re-crystallization etc. were optimised. Nearly 70% of lead contained by the waste material could be leached out and converted to lead(II) chloride. The product (PbCl2) was characterised by atomic absorption spectroscopy, thermogravimetric analysis, x-ray diffraction analysis, and scanning electron microscopy. Atomic absorption spectroscopic analysis showed that the product was 93% pure. X-ray diffraction analysis confirmed that the product possess cotunnite phase having orthorhombic structure. The needle like shape of the prepared PbCl2 crystal was confirmed by scanning electron microscopy. Physical properties like melting point and density were also very close to those reported in literature. Bangladesh J. Sci. Ind. Res. 47(4), 415-420, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14071